An innovative virtual-engineering system for supporting integrated footwear design. (4th June 2010) - Azariadis, Philip; Moulianitis, Vassilis; Melis, Jose Olaso; Alemany, Sandra; Gonzalez, Juan; Jong, Pamela; Dunias, Paraskevas; Zande, Marc; Brands, Dave
This paper presents a new virtual-engineering platform, called as virtual shoe test bed (VSTB), for supporting the design of footwear from the engineering point of view. The proposed VSTB system includes various functional design criteria in order to support the definition of the best solution for each product utilising scenarios based on user needs and preferences. Using the proposed virtual-engineering system a designer is able to simulate the behaviour of footwear components and the interaction between shoe and user in order to derive a predictive estimation of the fitting, thermal comfort and performance ratings without the necessity to manufacture and validate physical prototypes. The present paper describes the architecture, the tests implemented in the final system along with corresponding lab experiments conducted in terms of industrial validation. All results and hints for future research are reported and discussed.